2022
DOI: 10.1097/qco.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Update on pathogenesis, management, and control of Plasmodium vivax

Abstract: Purpose of reviewThis is a review of Plasmodium vivax epidemiology, pathogenesis, disease presentation, treatment and innovations in control and elimination. Here, we examine the recent literature and summarize new advances and ongoing challenges in the management of P. vivax. Recent findingsP. vivax has a complex life cycle in the human host which impacts disease severity and treatment regimens. There is increasing data for the presence of cryptic reservoirs in the spleen and bone marrow which may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In many countries, P. vivax malaria is a major public health problem, causing severe illness and economic hardships in remote populations. A growing number of studies have indicated severity, complications, and deaths due to P. vivax malaria in pregnant women and small children 2 , 3 . Compared to Plasmodium falciparum -caused disease, P. vivax malaria is harder to control and eliminate due to its ability to lie dormant as a hypnozoite in the human liver for months to years before it reactivates 4 and cause a relapse of blood-stage infection.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, P. vivax malaria is a major public health problem, causing severe illness and economic hardships in remote populations. A growing number of studies have indicated severity, complications, and deaths due to P. vivax malaria in pregnant women and small children 2 , 3 . Compared to Plasmodium falciparum -caused disease, P. vivax malaria is harder to control and eliminate due to its ability to lie dormant as a hypnozoite in the human liver for months to years before it reactivates 4 and cause a relapse of blood-stage infection.…”
Section: Introductionmentioning
confidence: 99%
“…It is transmitted to humans through the bite of the female Anopheles mosquito. There are five species of parasites that can cause malaria in humans, but Plasmodium falciparum and Plasmodium vivax are the greatest threat ( Figure 1 ) [ 27 ]. While malaria is a preventable and curable disease, without prompt diagnosis and effective treatment, an uncomplicated case of malaria can progress to a severe form of the disease, often leading to a fatal outcome if left untreated.…”
Section: Parasitic Infections With An Impact On the Populationmentioning
confidence: 99%